Teaching the eighteenth century - Rooks, Mary Ann (Cambridge Scholars, 2009)
Inspired by the conversations of like-minded professors interested in promoting eighteenth-century literature through informed, innovative teaching, this collection began as a series of presentations at the South Central Society for Eighteenth-Century Stu.